Twofold radical-based synthesis of N,C-difunctionalized bicyclo[1.1.1]pentanes - Pickford, HD; Nugent, J; Owen, B; Mousseau, JJ; Smith, RC; Anderson, EA (American Chemical Society, 2021)
Bicyclo[1.1.1]pentylamines (BCPAs) are of growing importance to the pharmaceutical industry as sp3-rich bioisosteres of anilines and N-tert-butyl groups. Here we report a facile synthesis of 1,3-disubstituted BCPAs using a twofold radical functionalization strategy. Sulfonamidyl radicals, generated through fragmentation of α-iodoaziridines, undergo initial addition to [1.1.1]propellane to afford iodo-BCPAs; the newly formed C–I bond in these products is then functionalized via a silyl-mediated Giese reaction. This chemistry also translates smoothly to 1,3-disubstituted iodo-BCPs. A wide variety of radical acceptors and iodo-BCPAs are accommodated, providing straightforward access to an array of valuable aniline-like isosteres.